2015
DOI: 10.1007/s10103-015-1846-y
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of energy dependent irradiation of red and green lights on proliferation of human umbilical cord matrix-derived mesenchymal cells

Abstract: Light-emitting diodes (LED) have recently been introduced as a potential factor for proliferation of various cell types in vitro. Nowadays, stem cells are widely used in regenerative medicine. Human umbilical cord matrix-derived mesenchymal (hUCM) cells can be more easily isolated and cultured than adult mesenchymal stem cells. The aim of this study was to evaluate the effect of red and green lights produced by LED on the proliferation of hUCM cells. hUCM cells were isolated from the umbilical cord, and light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In the current study, the effect of green and red lights on neural differentiation of hUCM cells was investigated. Some studies have reported that LED irradiation could improve cell proliferation 1 , 5 , 32 . Kim et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, the effect of green and red lights on neural differentiation of hUCM cells was investigated. Some studies have reported that LED irradiation could improve cell proliferation 1 , 5 , 32 . Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…To assess differentiation capacity of the isolated cells, third passage hUCM cells at a density of 2.5 × 10 4 cells/cm 2 were seeded onto glass slides with DMEM/F12 supplemented either with adipogenic (50 μg/ml indomethacin and 100 nM dexamethasone) or osteogenic (10 nM dexamethasone, 10 mM β-glycerophosphate and 50 μg/ml ascorbic acid,) differentiation medium for 18 days. The culture media were refreshed every 72 h. Adipogenic and osteogenic differentiations were detected with Oil red O and Alizarin red staining, respectively 1 , 49 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell density in proliferative and hypertrophy zones of growth plate cartilage in all groups were counted in all samples. Alcian blue and alizarin red [ 31 , 32 ] were used for specific staining of cartilage and bone tissues, respectively. Comparison and evaluation of chondrogenesis and osteogenesis were performed based on a spectrophotometric assay by extracting and quantifying the amount of stain absorbed by the sections in previous experiments.…”
Section: Methodsmentioning
confidence: 99%